АРСЕН РІЧИНСЬКИЙ – ЖИТТЯ ДЛЯ ЛЮДЕЙ ТА УКРАЇНИ (до 130-річчя з дня народження) - Мазур, П.; Мазур, Л. (Українські медичні вісті, 2023)
АРСЕН РІЧИНСЬКИЙ – ЖИТТЯ ДЛЯ ЛЮДЕЙ ТА УКРАЇНИ (до 130-річчя з дня народження)